Industrial Revolution 4.0 in the construction industry: Challenges and opportunities for stakeholders - Alaloul, W.S. (Ain Shams University, 2020)
The trend of digitization, automation and the increased use of Information and Communications Technology (ICT) have been envisioned as the main concept of the Industrial Revolution (IR) 4.0. Comparing the progressions between multiple industries, the construction industry is reluctant in incorporating these innovative technologies into its common practices despite the drastic developments demonstrated by the other industries. Numerous challenges exist from multiple aspects which prevent the engagement of IR 4.0 within the construction industry. A comprehensive review is conducted to identify the main problems which delay the implementation of IR 4.0 related technologies within the construction industry and opportunities attained in the long run. Then a questionnaire survey was conducted where the collected data was analyzed. This study shows that the critical factor affecting the successful implementation is the social and technical factors. However, all the contributing factors established a significant influence on the successful implementation despite the identified critical factor. Â© 2019 The Authors